Preoperative radiotherapy does not alter pre- and early postoperative serum CRP and albumin concentrations in colorectal cancer patients - Wysocki, Wojciech M.; Stasik, Zofia; Darasz, Zbigniew; Jakubowicz, Jerzy; Tarapacz, Jadwiga; Kulpa, Jan Kanty (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : We aimed to assess the alterations of serum C-reactive protein (CRP) and albumin levels in colorectal cancer patients who underwent preoperative radio(chemo)therapy and those who did not. Material and methods: The determinations of albumin and CRP were performed before and at 2, 3, 5 and 7 days after surgery in 60 colorectal cancer patients. 25 healthy subjects served as a reference group. For each patient the modified Glasgow Prognostic Score (mGPS) was calculated. Results: On the operation day CRP and albumin concentrations were not different in preoperatively treated or radiotherapy naI..ve patients. On postoperative day 2, 3, 5 and 7 no significant differences were observed between the two groups, with the only exception for albumin concentration, which was significantly higher on postoperative days 2 and 7 in the radiation naI..ve group. In all patients perioperative alterations of serum CRP level were significant at all time points (preoperatively vs. day 2, day 2 vs. day 3, day 3 vs. day 5, day 5 vs. day 7). The albumin decrease from the preoperative day to postoperative day 2 was significant, as was its increase from postoperative day 3 to 5. Conclusions : We have seen no differences in the CRP and albumin concentrations in preoperatively irradiated versus non-irradiated colorectal cancer patients on the day of surgery and on postoperative days 2, 3, 5 and 7. There were, however, significant concentration changes in the value of these two serum markers from preoperatively to postoperative day 2 and over the following postoperative week, but presumably related to the surgical trauma, not the neoadjuvant treatment.